2014
DOI: 10.1007/s11682-014-9311-2
|View full text |Cite
|
Sign up to set email alerts
|

Regional cortical thickness and subcortical volume changes in patients with metabolic syndrome

Abstract: Although previous studies have demonstrated an association between metabolic syndrome (MS) and changes in the integrity of cerebral white matter, no study has evaluated cortical thickness or subcortical volumes in MS with MRI. The purpose of our study was to investigate changes in cortical thickness and subcortical volume in an asymptomatic MS population. A total of 86 asymptomatic subjects (40 patients with MS and 46 subjects without MS) underwent 3T brain MRI scanning, and cortical thickness was compared bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
21
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 49 publications
5
21
0
Order By: Relevance
“…Neither Wolf et al. (2016c) nor Song et al (2015) identified this brain region previously in association with MetS; thus these results raise the possibility that genetic variation modifies the regions of the brain that are vulnerable to MetS-related pathology. The left rostral middle frontal gyrus is part of the dorsolateral prefrontal cortex (DLPFC; Kikinis et al, 2010), which is critical to cognitive control (i.e., executive functions; Burzynska et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Neither Wolf et al. (2016c) nor Song et al (2015) identified this brain region previously in association with MetS; thus these results raise the possibility that genetic variation modifies the regions of the brain that are vulnerable to MetS-related pathology. The left rostral middle frontal gyrus is part of the dorsolateral prefrontal cortex (DLPFC; Kikinis et al, 2010), which is critical to cognitive control (i.e., executive functions; Burzynska et al, 2012).…”
Section: Discussionmentioning
confidence: 62%
“…Song et al (2015) reported reduced cortical thickness primarily in parietal regions in MetS patients compared to controls. Further, our group recently showed in whole-brain analyses conducted in the same young veteran sample that is the focus of this investigation, that PTSD-related MetS was associated with reduced cortical thickness in bilateral temporal and parietal regions and in right frontal regions, including orbitofrontal cortex, rostral anterior cingulate cortex, and central sulcus, which divides frontal and parietal lobes (Wolf et al, 2016c).…”
mentioning
confidence: 98%
“…Song et al examined cortical and subcortical thickness and volumes and reported reduced thickness in entorhinal cortex, but not other MTL regions. Potential relationships between structural compromise and memory performance were not investigated [9]. In healthy adults, it has been shown that entorhinal and hippocampal shrinkage predicts episodic memory performance [10, 11].…”
Section: Introductionmentioning
confidence: 99%
“…We made the following four hypotheses: (1) Due to the relationship between MetS and AD and evidence of structural brain abnormalities associated with MetS, it was hypothesized adults with MetS would have smaller estimates of cortical thickness in MTL structures and smaller volumes of the hippocampus relative to controls [3, 4, 9]; (2) Given previous findings showing relationship between cortical thickness and number of MetS risk factors, it was hypothesized cortical thickness in MTL and the entorhinal cortex, and hippocampal volume would be associated with the number of MetS risk factors [7]; (3) It was hypothesized cortical thickness in MTL structures and hippocampal volume would be associated with memory performance as these structures are critical to memory function [8]; and (4) Given previous evidence showing that MetS is associated with reduced entorhinal cortex [9] and other structural abnormalities [6], and evidence demonstrating relationships between MTL and memory decline, it was hypothesized that the relationship between MetS and memory performance would be mediated by structural changes in the MTL.…”
Section: Introductionmentioning
confidence: 99%
“…MetS may cause complications in the brain: In an animal study, chronic hyperglycemia and insulin resistance were reported as risk factors for neuronal death through induction of a state of oxidative stress and inflammatory response, thus affecting cognitive processes [23]. Patients with MetS showed a significant reduction in mean cortical thickness and volume in both hemispheres compared with controls, suggesting an initial neurodegenerative process and cognitive deterioration with MetS, even at a preclinical stage [24]. Furthermore, four studies of topiramate as an add-on therapy in patients with bipolar disorder showed that weight reduction is associated with a significant reduction in both depressive and manic symptoms [2528].…”
Section: Introductionmentioning
confidence: 99%